THE IMPACT OF SHORTENED PRODUCT LAUNCH SCHEDULES ON THE TENDERING PROCESS IN THE PROPERTY INDUSTRY - Retno santoro; Jerry Haikal (PT. Media Akademik Publisher, 2024)
The timing of product launches in the property industry is a strategic element that plays a significant role in overall project management and business sustainability. However, overly tight launch schedules can often trigger various problems during the tendering phase, particularly in selecting the right contractor aligned with the company's vision of creating high-quality products. One of the primary issues in accelerated tender processes is the inaccuracy of cost estimates, as limited time restricts the ability to conduct detailed and accurate calculations. Moreover, the quality of work often deteriorates due to limited time for thorough planning and execution. This condition also has the potential to exacerbate oversight processes and disrupt the overall project timeline. This study aims to understand the concrete impact of urgent launch schedules on the tendering process in property development projects. A grounded theory approach was employed as a research method to know deeply into the data through interviews with practitioners experienced in the field of tendering. Through this research, five themes and nine categories were identified as the impacts of short tender schedules. The themes collected were related to Cost, Tender Quality, Time, Vendor Quality, Company Culture, Company Regulation and Work Productivity. Of these themes, Cost had the highest frequency compared to the others. Therefore, it is hoped that this research will serve as a consideration for management in the property business before setting product launch schedules without compromising marketing strategies.